Difficulties in the diagnosis of Lyme disease in children. Clinical case - G. S. Karpovich; D. S. Maramygin; Yu. S. Serova; E. I. Krasnova; I. V. Kuimova (Лечащий Врач, 2022)
Ixodid tick-borne borreliosis (Lyme disease) is an infectious disease common in areas inhabited by borrelias – potential causative agents of this pathology. Currently, about 20 genospecies of Borrelia are known, pathogenicity for humans has been proven for 4 of them, but this number continues to grow. The transmissible mechanism of transmission makes it possible to classify this disease as a natural focal infection, which makes this problem particularly relevant for the territory of Siberia and the Far East. The wide polymorphism of clinical manifestations, the complexity of specific diagnostics and the lack of information both for doctors and the general population often make it difficult to verify the diagnosis and often lead to late diagnosis, which carries the risk of developing chronic forms of the disease. Neurological manifestations of Lyme disease in children are usually characterized by the development of lesions of the central nervous system. Neuroborreliosis in pediatric practice is usually characterized by the development of serous inflammation of the dura mater, but requires specific antibiotic therapy. Late diagnosis of neuroborreliosis entails an increase in the number of complications and more frequent development of neurological deficit in the outcome of the pathological process. The article provides an observation of a clinical case of the development of Lyme disease in a child, characterized by a lesion of the central nervous system in the form of serous meningitis. Noteworthy is the absence of a verified fact of tick bite, an atypical course of the disease with an initial lesion of the central nervous system and the subsequent formation of a typical annular erythema. The delayed formation of the cardinal symptom of Lyme disease in the form of erythema annulare in the above clinical observation seriously complicates timely diagnosis, and makes it virtually impossible in the absence of the doctor's alertness and the availability of specific highly selective methods of etiotropic diagnosis. In addition, the article also demonstrates the difficulties of differential diagnosis against a comorbid background.